Local probe techniques for corrosion research - Oltra, R. (Woodhead Publishing Limited : CRC Press, 2007)
The effective investigation of corrosion requires the use of methods that can probe material surfaces at the atomic or molecular level and can be used in situ. This important collection reviews the range of techniques available and how they can be used to analyse different types of corrosion. A number of chapters discuss the use of scanning probe microscopy techniques such as electrochemical scanning tunnelling microscopy and atomic force microscopy (EC-STM and EC-AFM). Other chapters analyse local electrochemical techniques such as scanning electrochemical microscopy (SECM), scanning vibrating electrode techniques (SVET), scanning droplet and scanning kelvin probe microscopy (SKFM), as well as microraman spectroscopy and photoelectrochemical imaging. The book reviews the application of these techniques in practice to various metals and types of coating as well as different kinds of corrosion. With its distinguished editors and team of contributors, this is a valuable reference for all those concerned with corrosion research. Discusses methods that can probe material surfaces at the atomic or molecular levelA valuable reference for all those concerned with corrosion research.
"Published for the European Federation of Corrosion by Woodhead Publishing and Maney Publishing on behalf of The Institute of Materials, Minerals & Mining."
Keywords: Corrosion and anti-corrosives.; Scanning probe microscopy.; Spectrum analysis.; elektronické knihy; electronic books